Answer:
For this case we have the following functions transformation:
Vertical expansions:
To graph y = a * f (x)
If a> 1, the graph of y = f (x) is expanded vertically by a factor a.
f1 (x) = (3x) ^ 2
Horizontal translations
Suppose that h> 0
To graph y = f (x-h), move the graph of h units to the right.
f2 (x) = (3x-6) ^ 2
Vertical translations
Suppose that k> 0
To graph y = f (x) + k, move the graph of k units up.
g (x) = (3x-6) ^ 2 + 3
Answer:
expanded horizontally by a factor of 3, horizontal shift rith 6, vertical shift up 3